Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/nn.3933
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-driven discovery of epilepsy genes

Abstract: Epilepsy genes deliver critical insights into the molecular control of brain synchronization and are revolutionizing our understanding and treatment of the disease. The epilepsy-associated genome is rapidly expanding, and two powerful complementary approaches, isolation of de novo exome variants in patients and targeted mutagenesis in model systems, account for the steep increase. In sheer number, the tally of genes linked to seizures will likely match that of cancer and exceed it in biological diversity. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
115
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(122 citation statements)
references
References 98 publications
4
115
0
1
Order By: Relevance
“…Indeed, genetic analysis of specific forms of inherited epilepsy, along with GenomeWide Association Studies (GWAS) and exome sequencing studies of large cohorts of epilepsy patients and controls, have identified epilepsy-associated sequence variants in hundreds of genes with a wide variety of roles in nervous system development and function (Noebels, 2015). Many of these genes encode neuronal proteins that regulate membrane excitability, such as ion channels, neurotransmitter receptors and transporters (Deng et al, 2014), or factors controlling synaptic vesicle formation, release and trafficking (Casillas-Espinosa et al, 2012).…”
Section: The Need For New In Vivo Experimental Models Of Epilepsy Q3mentioning
confidence: 99%
“…Indeed, genetic analysis of specific forms of inherited epilepsy, along with GenomeWide Association Studies (GWAS) and exome sequencing studies of large cohorts of epilepsy patients and controls, have identified epilepsy-associated sequence variants in hundreds of genes with a wide variety of roles in nervous system development and function (Noebels, 2015). Many of these genes encode neuronal proteins that regulate membrane excitability, such as ion channels, neurotransmitter receptors and transporters (Deng et al, 2014), or factors controlling synaptic vesicle formation, release and trafficking (Casillas-Espinosa et al, 2012).…”
Section: The Need For New In Vivo Experimental Models Of Epilepsy Q3mentioning
confidence: 99%
“…As such, the mechanisms of disease will continue to be elucidated. This progression in unraveling complex genetic diseases is illustrated by the pathway-driven discovery of epilepsy genes 5 and by the discernment of gene networks associated with autism. 6 …”
Section: Increasing Ngs Sensitivity To Improve Diagnosis Ratesmentioning
confidence: 99%
“…98,99 In mice and humans, a combination of empirical evidence and literature review has begun to define the circuitry of networks associated with disease. 100,101 In many species, modifier genes are readily identified for both simple and complex traits. With these emerging resources and technologies, specifying network components, their dependencies, and targets for interventions is increasingly feasible, especially for specific conditions and diseases.…”
mentioning
confidence: 99%